A clinical profile of poisonous snake bite in children of North Kerala, India - K. P., Shyna; K., Sudhakaran; M. T. P., Mohammed (International Journal of Contemporary Pediatrics, 2018)
Background: Snake bite is a common medical emergency and underestimated public health problem causing significant morbidity and mortality worldwide. Poisonous snake bite is a common problem in north Kerala and a significant number of children are bitten by snakes every year. Majority of studies in this respect have been done on adult snake bite victims and only limited studies are available based on poisonous envenomation in children in our region. The clinical profile of snake bite in children can differ significantly from adult snake bite victims so study was conducted to find the clinical profile of poisonous snake bite in children less than fifteen years. Methods: This was a descriptive cross sectional study conducted in a tertiary care academic institution located in the northern part of Kerala from December 2009 to November 2010. All children less than 15 years with poisonous snake bite were included in this study. Patients with non-poisonous bite, without signs of envenomation and with pre-existing bleeding and renal disorders were excluded. Results: There were fifty cases of poisonous snake bite and among them 76% were males and 24% were females. The highest numbers of bites (50%) occurred in the age group between 11-15 years. Maximum number of snake bite occurred during the months of June and July. The majority of the bites occurred during night between 6 pm to 9 pm (42 %). Among the identified venomous bite Viper accounted for the highest number (48%), followed by Krait (12 %) and Cobra (4%). Lower extremities were the most observed bitten part of the body (82%) and the commonest site was foot. Eighty four percentage of victims reached hospital within 6 hours of snake bite. The most common clinical manifestation was local pain (94%) followed by swelling (90%) and regional lymphadenopathy (82%). Majority had hemotoxicity (94%) and neurotoxicity (6%) was comparatively lesser in our study. Most common complication was overt bleeding manifestations (14%) followed by gangrene of bite site (8%), acute kidney injury (6%) and respiratory paralysis (2%). Thirty eight percent of cases required more than 10 vials of ASV and reaction to ASV occurred in 40% of cases. No mortality occurred during this study period. Conclusions: Poisonous snake bite is a common life threatening medical emergency in our region. Morbidity and mortality due to this can be reduced by early administration of anti-snake venom and prompt recognition and management of complications. So, prompt referral of children with poisonous snake bite to centres where facilities in managing snake bite is crucial in preventing mortality.